An exam of the role of the geographical proximity for the university-industry linkages - Renato Garcia; Veneziano Araujo; Suelene Mascarini (European Regional Science Association (ERSA), 2010)
It is widely recognized in the literature that the clustering of firms can generate benefits for the local firms, especially in terms of the creation and diffusion of knowledge among producers. One of the main sources of this new knowledge is the academic research, which can contribute to the innovative efforts of the firms, mainly when researchers in university and industry can cooperate by build joint research projects. Many authors (Audrescht and Feldman, 1996; Acs and Varga, 2005; Breschi and Lissoni, 2009) have shown that academic research is positively correlated with firms' innovation at the geographical level. There are two reasons that are pointed out for this correlation. First, there are many ways in which knowledge generated by academic research can spill over to the firms, such as papers, patents and informal contacts. Second, geographical proximity can encourage cooperation between academic researchers and the R&D staff in the firms. Based on these statements, it was done an empirical research by using data from the Brazilian Research Council (CNPq), collected at the CNPq Directory of Research Groups of Brazilian universities. This database allows the identification of 2,151 interactive research groups, among 19,470, that declared that they have interactions with 3,068 firms. By the localization of both firms and university research groups, it was possible to gather information about the geographical pattern of university-industry linkages.
Keywords: 330; knowledge spillovers; industrial clusters; university-industry linkages